Molecular engineering of functionalized crown ether resins for the isotopic enrichment of gadolinium: from computer to column chromatography. Issue 5 (25th October 2017) - Boda, A.; Singha Deb, A. K.; Ali, Sk. M.; Shenoy, K. T.; Mohan, S.
Abstract : Computer aided molecular engineering of functionalized crown ethers for isotope separation of gadolinium using column chromatography. Abstract : Density functional theoretical modelling was performed to design and screen suitable macrocyclic crown ether functionalized resins for the isotopic enrichment of gadolinium. Theoretical calculations predict the complexation stability order of Gd 3+ ion as follows: di-cylohexano-18-crown-6 (DCH18C6) > dibenzo-18-crown-6 (DB18C6) > benzo-15-crown-5 (B15C5), which was experimentally verified. The calculated isotopic separation factor value was shown to be the highest for DB18C6. From the theoretical analysis of both the stability and isotopic separation factor, DB18C6 is predicted to be the most promising candidate for isotopic separation of gadolinium. Hence, DB18C6 was functionalized with chloromethylated polystyrene (CMPS) resin. Subsequently, CMPS-grafted DB18C6 resin was synthesized and characterized. Furthermore, isotopic enrichment of gadolinium was carried out by performing column chromatographic experiments using CMPS-DB18C6 resin. The absorption capacity of the novel CMPS-DB18C6 resin for gadolinium was found to be 1 mg g −1 . The separation coefficient, ε × 10 3, was found to be 6.3, 8.9, 3.4, and 9.7 for Gd-155/158, Gd-156/158, Gd-157/158, and Gd-155/160 isotopic pairs, respectively, and thus hold promise for future isotopic enrichment technology.